He huarahi motuhake : the politics of tribal agency in provider services : submitted in fulfilment of the requirement of the degree of Doctor of Philosophy, Te Pūtahi a Toi, School of Māori Studies, Massey University, Palmerston North, New Zealand - Jahnke, Huia (Massey University. School of Maori Studies, 2005)
This thesis explores the nature of tribal service provision, in particular the characteristics that distinguish tribal provider services. An indigenous research paradigm, Mäori philosophical traditions and tribal histories provide the context for researching and theorising about the three tribal organisations upon which this study is based. The thesis argues that tribal authorities emerged not only as a response to state policies of devolution but also as ongoing expressions of self-determination. How tribal organisational bureaucracies were established historically provides the context for examining the interface between tribal organisations and the state. In particular, specific historical events leading up to the 1840 annexation of New Zealand by Britain that demonstrate British assumptions of authority, humanitarian ideals and interventions by state functionaries in the affairs of New Zealand.A discussion on the nature of the state as the basis for Eurocentric bias in modern constitutionalism offers a platform for understanding the art of government. Four interconnecting themes give a systematic basis for exploring the distinctive characteristics of tribal provider services that emerged as significant in this study; 'ngä mahi a ngä tangata' examines advocacy, responsiveness and relevancy. 'Ngä mahi mä te iwi' considers how links to the Mäori communities are constituted relative to whänau, hapü and marae. 'Ngä mahi a ngä tipuna' explores how culture counts and the place of Mäori culture and traditions in the workplace. 'Ngä mahi tuara' examines cultural frameworks located within Mäori philosophical and customary practices and traditions.Finally, an analysis is given of the contracting environment and the counterstrategies employed by the participants in this study in countering the limitations imposed by the terms of state contracts.
Keywords: Maori development; Maori service provision; Indigenous governance; Indigenous studies; Māori Doctoral Thesis; 420306 Maori cultural studies